A method for preparing a lithium-stable sulfide composite electrolyte membrane and a lithium battery

By spraying a nitrogen phosphide electrolyte layer on the surface of the sulfide electrolyte membrane, a stable compound is generated, which solves the problem of unstable contact between the sulfide electrolyte and lithium, and improves the stability and energy density of the lithium battery.

CN117317345BActive Publication Date: 2025-01-14SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311545746.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2025-01-14
Estimated Expiration
2043-11-17

AI Technical Summary

Technical Problem

When the sulfide electrolyte comes into contact with metal lithium, a decomposition reaction occurs, generating non-uniformly distributed components and metal lithium dendrites, resulting in a short circuit in the battery. The stability of lithium still needs to be improved in the prior art.

Method used

Using nitrogen phosphide electrolyte as the intermediate layer between electrolyte and lithium, spraying the nitrogen phosphide electrolyte layer on the surface of the sulfide electrolyte membrane to generate compounds such as Li3N, LiF, LiCl, LiBr, etc., inhibit the growth of lithium dendrites, and pass ball milling and rolling pressure. Form a stable sulfide composite electrolyte membrane.

Benefits of technology

It improves the stability of lithium and electrolytes, inhibits the growth of lithium dendrites, and optimizes the energy density and cycling performance of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117317345B_ABST
    Figure CN117317345B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a sulfide composite electrolyte membrane that is stable to lithium and a lithium battery. The preparation method is as follows: a nitrogen phosphide electrolyte solution is sprayed on the surface of a sulfide electrolyte layer to form a spray layer, and the sulfide composite electrolyte membrane is obtained by drying. When assembled into a battery, one side of the spray layer is close to the negative electrode. The present invention aims to solve the problem of instability in contact between electrolyte and lithium, which causes lithium dendrites and further causes battery short circuit. 10 P 4 N 10 and Li 13 P 4 N 10 X 3 , X=Cl, Br, F) as the negative electrode contact layer, and metallic lithium generate a nitrogen-rich SEI film, which widens the nitride electrolyte window and is thermodynamically stable to lithium; the nitrogen phosphide electrolyte and lithium generate lithium nitride and lithium phosphide during the charge and discharge process, which improves the stability of the SEI film and optimizes the solution of metallic lithium as the negative electrode. On this basis, the energy density of all-solid-state batteries can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium batteries, and specifically relates to a method for preparing a lithium-stable sulfide composite electrolyte membrane and a lithium battery. Background Art

[0002] Although sulfide electrolytes have high room temperature conductivity (>10 -3 S / cm), but sulfide electrolytes have lower thermodynamic stability and narrower electrochemical window (1.7-2.4V). Therefore, when sulfide electrolytes come into contact with metallic lithium, decomposition reactions will occur to generate non-uniformly distributed components such as lithium sulfide and lithium phosphide. At the same time, due to the uneven distribution of charge, the growth of metallic lithium dendrites will also cause battery short circuit.

[0003] In all-solid-state batteries with sulfide as electrolyte, in order to solve the above problems, 1) alloy negative electrode is used to replace metallic lithium, 2) the surface of the lithium negative electrode is modified, and 3) the electrolyte is modified. CN110911733A reports that the surface of the argyrodite sulfide solid electrolyte is coated with a shell composed of LiPS compounds. By adopting the above technical scheme, the LiPS compounds are generally LiPS or LiPS lithium-deficient sulfur-phosphorus compounds, which are relatively stable with metallic lithium. CN115513518A reports a method for doping electrolytes to prepare lithium-stable electrolytes. CN114242958A improves the stability of lithium and electrolytes by polymer modification of the lithium surface. However, the lithium stability of the electrolytes in the above patents needs to be improved. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a lithium-stable sulfide composite electrolyte membrane and a lithium battery in view of the problems existing in the prior art.

[0005] The purpose of the present invention can be achieved by the following scheme:

[0006] The present invention provides a method for preparing a lithium-stable sulfide composite electrolyte membrane, comprising the following steps:

[0007] The nitrogen phosphide electrolyte solution is sprayed on the surface of the sulfide electrolyte layer to form a spray layer (nitrogen phosphide electrolyte layer), and the sulfide composite electrolyte membrane is obtained by drying. When assembled into a battery, one side of the spray layer is close to the negative electrode.

[0008] As one embodiment of the present invention, the nitrogen phosphide electrolyte includes Li 10 P4N 10 , Li 13 P4N 10One of X3, X = Cl, Br, F. The present invention uses a nitrogen phosphide electrolyte as an intermediate layer between the electrolyte and lithium, which can be decomposed in situ on the lithium surface to generate Li3N and Li3P. 13 P4N 10 X3 can also generate LiF, LiCl, LiBr, etc. in situ. The above products are all compounds with good affinity for lithium and are helpful in inhibiting lithium dendrites.

[0009] As an embodiment of the present invention, the solvent of the nitrogen phosphide electrolyte solution includes one or more of xylene, n-hexane, and anisole, and the concentration of the nitrogen phosphide electrolyte is 0.1-0.5 mg / ml.

[0010] As an embodiment of the present invention, the thickness of the nitrogen phosphide electrolyte layer on the surface of the sulfide composite electrolyte membrane is 5-20 μm.

[0011] As an embodiment of the present invention, the drying parameters are 60-100° C. and the time is 5-24 hours.

[0012] As an embodiment of the present invention, the sulfide electrolyte includes one or more of argyrodite-type, lithium-germanium-phosphosulfur-type, Li2S-P2S5-type, and thio-LISICON-type electrolytes.

[0013] As one embodiment of the present invention, the preparation method of the sulfide electrolyte layer is as follows:

[0014] (1) ball milling the sulfide electrolyte in a protective atmosphere;

[0015] (2) adding a binder to the ball-milled sulfide electrolyte and continuing the ball milling;

[0016] (3) The treated sulfide electrolyte is rolled into a film in an argon glove box to obtain the sulfide electrolyte layer with a thickness of 100 μm.

[0017] In step (1), the ball milling is specifically ball milling in a zirconium oxide ball milling jar; the ball-to-material ratio is 5-15:1, the rotation speed is 300-500 rpm, and the ball milling time is 6-10 hours. The protective atmosphere of the ball milling is argon gas.

[0018] In step (2), the ball milling parameters are: the rotation speed is 300-500 rpm, the ball milling time is 1-2 hours, and the adhesive is PTFE.

[0019] In step (3), the thickness of the sulfide electrolyte layer is 50-150 μm.

[0020] In steps (1) and (2), the mass ratio of electrolyte to adhesive is 400-600:1.

[0021] The present invention also provides a lithium battery, comprising a positive electrode, a negative electrode and an electrolyte layer; the electrolyte layer is the lithium-stable sulfide composite electrolyte membrane, the negative electrode is a lithium foil, and one side of the spray layer of the sulfide composite electrolyte membrane is close to the lithium negative electrode.

[0022] As an embodiment of the present invention, the composite positive electrode is a composite positive electrode prepared from sulfide electrolyte, NCM811, and VGCF.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention aims to solve the problem of instability in contact between electrolyte and lithium, which causes lithium dendrites and then battery short circuit. 10 P4N 10 and Li 13 P4N 10 X3, X=Cl, Br, F) as the negative electrode contact layer, and metal lithium to form a stable SEI film;

[0025] (2) Nitrogen-phosphide electrolyte reacts with lithium to generate lithium nitride and lithium phosphide during the charge and discharge process, which improves the stability of the SEI film and optimizes the scheme of using metallic lithium as the negative electrode. On this basis, the energy density of all-solid-state batteries can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0027] Figure 1 Schematic diagram of the preparation method of the sulfide composite electrolyte membrane of the present invention;

[0028] Figure 2 Conductivity bar graphs of different embodiments and comparative examples;

[0029] Figure 3 Limiting current density and polarization voltage curves of different embodiments and comparative examples;

[0030] Figure 4 Cycling performance curves of all-solid-state batteries of different embodiments and comparative examples. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0032] Example 1

[0033] This embodiment provides a lithium-stable sulfide composite electrolyte membrane and a lithium battery, and the preparation steps are as follows:

[0034] 1. Mill 5000mg Li6PS5Cl electrolyte in a 100ml zirconia ball mill. The ball-to-material ratio is 10:1, the rotation speed is 400rpm, the ball milling time is 8h, and the experiment is carried out under argon atmosphere;

[0035] 2. Add 10 mg PTFE to the ball-milled electrolyte and continue ball-milling at a speed of 400 rpm for 1 h. The reaction is carried out under argon.

[0036] 3. Roll the treated electrolyte into a film in an argon glove box with a thickness of 100 μm;

[0037] 4. Take 10 mg Li 10 P4N 10 Dispersed in 50 ml of xylene solvent, such as Figure 1 As shown, it was sprayed on the electrolyte surface of step 3, with a spraying thickness of 5 μm, and dried in a glove box (80° C., 8 h);

[0038] 5. Test the conductivity of the dried electrolyte. Cut it into 10mm diameter discs, use stainless steel as blocking electrode, test the electrochemical AC impedance, the test conditions are: 7M Hz ~ 0.1Hz, disturbance voltage is 10mV, such as Figure 2 As shown, the conductivity is 7.7 mS / cm;

[0039] 6. Use 50 μm thick and 10 mm diameter lithium foil as positive and negative electrodes, and the electrolyte membrane dried in step 4 as the electrolyte layer to assemble the pressure battery, such as Figure 3 As shown, the test limit current density is 0.85mA / cm 2 , polarization voltage is 20mV;

[0040] 7. Prepare a composite positive electrode with Li6PS5Cl, NCM811, and VGCF in a mass ratio of 40:55:5, and grind in a glove box for 30 minutes. Take 10 mg of the composite positive electrode, use the electrolyte membrane dried in step 4 as the electrolyte layer, and 50 μm thick lithium as the negative electrode to prepare a 10 mm diameter pressure battery, with the spray layer close to lithium. Test the battery charge and discharge performance at room temperature, such as Figure 4 As shown, the test voltage range is 2.8~4.3V and the test pressure is 10MPa.

[0041] Example 2

[0042] This embodiment provides a lithium-stable sulfide composite electrolyte membrane and a lithium battery, and the preparation steps are as follows:

[0043] 1. Mill 5000mg Li6PS5Cl electrolyte in a 100ml zirconia ball mill. The ball-to-material ratio is 10:1, the rotation speed is 400rpm, the ball milling time is 8h, and the experiment is carried out under argon atmosphere;

[0044] 2. Add 10 mg PTFE to the ball-milled electrolyte and continue ball-milling at a speed of 400 rpm for 1 h. The reaction is carried out under argon.

[0045] 3. Roll the treated electrolyte into a film in an argon glove box with a thickness of 100 μm;

[0046] 4. Take 10 mg Li 13 P4N 10 F3 was dispersed in 50 ml of xylene solvent, sprayed on the surface of the electrolyte in step 3 with a spraying thickness of 5 μm, and dried in a glove box (80°C, 8h);

[0047] 5. Test the conductivity of the dried electrolyte. Cut it into a disc with a diameter of 10 mm, use stainless steel as a blocking electrode, and test the electrochemical AC impedance. The test conditions are: 7M Hz ~ 0.1Hz, disturbance voltage is 10mV, and the conductivity is 7.5mS / cm

[0048] 6. Use 50μm thick and 10mm diameter lithium foil as positive and negative electrodes, and the electrolyte membrane dried in step 4 as the electrolyte layer. Assemble the pressure battery and test the limiting current density to 0.85mA / cm 2 , polarization voltage is 20.9mV;

[0049] 7. Prepare a composite positive electrode with Li6PS5Cl, NCM811, and VGCF in a mass ratio of 40:55:5, and grind in a glove box for 30 minutes. Take 10 mg of the composite positive electrode, use the electrolyte membrane dried in step 4 as the electrolyte layer, and 50 μm thick lithium as the negative electrode to prepare a 10 mm diameter pressure battery, with the spray layer close to lithium. Test the battery charge and discharge performance at room temperature, the test voltage range is 2.8~4.3V, and the test pressure is 10MPa.

[0050] like Figure 4 As shown, the release specific capacity and cycle stability of the all-solid-state batteries of Example 1 and Example 2 are better than those of Comparative Examples 1 to 3.

[0051] Comparative Example 1

[0052] This comparative example provides a lithium-stable sulfide composite electrolyte membrane and a lithium battery, and the preparation steps are as follows:

[0053] 1. Mill 5000mg Li6PS5Cl electrolyte in a 100ml zirconia ball mill. The ball-to-material ratio is 10:1, the rotation speed is 400rpm, the ball milling time is 8h, and the experiment is carried out under argon atmosphere;

[0054] 2. Add 10 mg PTFE to the ball-milled electrolyte and continue ball-milling at a speed of 400 rpm for 1 h. The reaction is carried out under argon.

[0055] 3. Roll the treated electrolyte into a film in an argon glove box with a thickness of 100 μm;

[0056] 4. Cut the product in step 3 into a disc with a diameter of 10 mm, use stainless steel as the blocking electrode, and test the electrochemical AC impedance. The test conditions are: 7 MHz ~ 0.1 Hz, disturbance voltage of 10 mV, and conductivity of 8.1 mS / cm;

[0057] 5. Use 50μm thick and 10mm diameter lithium foil as positive and negative electrodes, and the electrolyte membrane of step 3 as the electrolyte layer to assemble the pressure battery. The test limit current density is 0.3mA / cm 2 , polarization voltage is 33.7mV;

[0058] 6. Prepare a composite positive electrode with Li6PS5Cl, NCM811, and VGCF in a mass ratio of 40:55:5, and grind in a glove box for 30 minutes. Take 10 mg of the composite positive electrode, use the electrolyte membrane in step 3 as the electrolyte layer, and 50 μm thick lithium as the negative electrode to prepare a 10 mm diameter pressure battery. Test the battery charge and discharge performance at room temperature, with a test voltage range of 2.8 to 4.3 V and a test pressure of 10 MPa.

[0059] Comparative Example 2

[0060] This comparative example provides a method for preparing a sulfide composite electrolyte membrane that is stable to lithium and a lithium battery. The preparation method is basically the same as that of Example 1, except that: the sulfide composite electrolyte membrane Li 10 P4N 10 Replaced with Li3N. The conductivity is 7.0mS / cm, which is much lower than that of Example 1 and Example 2. The test limiting current density is 0.45mA / cm 2 , lower than Example 1 and Example 2, the polarization voltage is 28mV.

[0061] Lithium nitride is an important component of the lithium negative electrode SEI film. Adding Li3N (or other metal nitrides) between lithium and electrolyte can improve the stability of the negative electrode. However, since this method is non-in-situ growth of Li3N, there will be certain microscopic gaps between Li3N and lithium. The gaps are defects. As the battery cycle lengthens, lithium dendrites will continue to grow at the defects. Non-in-situ addition of LiI and Li5NI2 between lithium and electrolyte will also have such problems.

[0062] Comparative Example 3

[0063] This comparative example provides a method for preparing a sulfide composite electrolyte membrane that is stable to lithium and a lithium battery. The preparation method is basically the same as that of Example 1, except that: the sulfide composite electrolyte membrane Li 10 P4N 10 Replaced with LiPON. Due to the low conductivity of LiPON itself, the conductivity of the composite electrolyte membrane is 6.0mS / cm, which is much lower than that of Example 1 and Example 2. The test limiting current density is 0.45mA / cm 2 , which is lower than that of Example 1 and Example 2, and the polarization voltage is 35.7 mV.

[0064] As a type of solid electrolyte, LiPON has a certain affinity for lithium and has been shown to be able to serve as a lithium metal protective layer. However, the room temperature conductivity of LiPON is about 10 -6 S / cm, lower conductivity affects ion transport and increases impedance.

[0065] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a lithium-stable sulfide composite electrolyte membrane, characterized in that: The method comprises the following steps: spraying a nitrogen phosphide electrolyte solution on the surface of a sulfide electrolyte layer to form a spray layer, and drying the layer to obtain the sulfide composite electrolyte membrane; Nitrogen phosphide for Li 10 P4N 10 , Li 13 P4N 10 One of X3, X includes one of Cl, Br, and F.

2. The preparation method according to claim 1, characterized in that: The solvent of the nitrogen phosphide electrolyte solution includes one or more of xylene, n-hexane, and anisole, and the concentration of the nitrogen phosphide electrolyte is 0.1-0.5 mg / ml.

3. The preparation method according to claim 1, characterized in that: The thickness of the sprayed layer is 5-20 μm.

4. The preparation method according to claim 1, characterized in that: The drying temperature is 60-100°C and the drying time is 5-24 hours.

5. The preparation method according to claim 1, characterized in that: The sulfide electrolyte includes one or more of argyrodite type, lithium germanium phosphosulfur type, Li2S-P2S5 type, and thio-LISICON type electrolytes.

6. The preparation method according to claim 1, characterized in that: The preparation method of the sulfide electrolyte layer is as follows: (1) ball milling the sulfide electrolyte in a protective atmosphere at a speed of 300-500 rpm for 6-10 hours; (2) Adding a binder to the ball-milled sulfide electrolyte and continuing ball milling at a speed of 300-500 rpm for 1-2 hours; (3) Roll-pressing the treated sulfide electrolyte into a film to obtain the sulfide electrolyte layer.

7. The preparation method according to claim 6, characterized in that: In step (3), the thickness of the sulfide electrolyte layer is 50-150 μm.

8. A lithium battery, characterized in that: It comprises a positive electrode, a negative electrode and an electrolyte layer; the electrolyte layer is a sulfide composite electrolyte membrane obtained by the preparation method according to any one of claims 1 to 7, the negative electrode is a lithium foil, and one side of the spray layer of the sulfide composite electrolyte membrane is close to the lithium negative electrode.

9. The lithium battery according to claim 8, characterized in that: The positive electrode is a composite positive electrode prepared by mixing a sulfide electrolyte, NCM811 and VGCF.

Citation Information

Patent Citations

  • Sulfide solid electrolyte stable to lithium, preparation method thereof and solid-state battery with solid electrolyte

    CN110911733A

  • Method for modifying lithium metal interface in sulfide solid-state battery and application

    CN114242958A

  • Sulfide solid electrolyte stable to solvent and lithium as well as preparation method and application of sulfide solid electrolyte

    CN115513518A

  • All-solid-state lithium metal battery and preparation process thereof

    CN109818048A

  • Binary phosphorus nitride protective solid electrolyte intermediary structures for electrode assemblies

    US20230091921A1